Testing Novel Water Oxidation Catalysts for Solar Fuels Production - Ottone, Carminna; Hernández, Simelys; Armandi, Marco; Bonelli, Barbara (PoliTO Springer Series, 2019)
This book offers comprehensive information on the main techniques for measuring water-oxidation-catalyst (WOC) performance, with a particular focus on the combined use of sacrificial oxidants and dyes within closed-batch reactors. It provides an overview of the latest advances in the synthesis of more efficient WOCs, followed by an analysis of the requirements for sustainable energy production. Readers will find a detailed description of the reaction mechanism used in catalyst assessment systems, which reveals the benefits and limitations of the most common sacrificial oxidant/dye pair. Experimental techniques including electrochemical methods for characterizing novel and non-photoactive WOCs are also described. Throughout the book, various manganese oxides are used as examples of the techniques reviewed or proposed systems. Cost considerations and technological perspectives of the scale-up of solar-driven hydrogen production are also addressed. Lastly, the book presents lessons learned from the implementation of a large-scale real-world device.